(untitled) (Fiep Bulletin - online, 2012)
Introduction: Cerebral Palsy is also called Chronic Encephalopathy of Infancy and is characterized by motor disorders of non progressive characteristics. The motor disorder is closely related to the area of the Central Nervous System that was injured. Spasticity is a clinical manifestation that frequently interferes with the rehabilitation of children with Cerebral Palsy. Commonly, in order to obtain a better physiotherapeutic action, the clinical staffs have adopted the use of botulinum toxin type A associated with the physiotherapeutic approach. The treatment is based on the control of spasticity making use of medicaments and kinesiotherapy. Among the medicaments that are used as medical blocks, the use of bolulinum toxin has stood out, which aims to cause the reduction of muscle tone and improve the motor control. It is believed that the association of the effect of BTA with the physiotherapeutic treatment may provide the increase of the amplitude of movement, decrease of muscle tone, favoring the adequate positioning, thus, improving the functionality of children with cerebral palsy. Aim: It is believed that the association of the effect of BTA with the therapeutic treatment may provide the increase of amplitude of movement, the decrease of muscle tone, favoring the adequate positioning, thus, improving the functionality of children with CP. However, there are few studies about this type of treatment. Due to the identification of the blank in previous investigations, this study evaluated the effect of the application of BTA associated with the physiotherapeutic treatment in the modulation of muscle tone and gain of amplitude of movement. Methodology: A case study of longitudinal cut, with quantitative approach. An eight-year-old child carrier of diplegic spastic cerebral palsy participated in this study. The evaluation of muscle tone of MMII was accomplished through the spasticity scale of Durigon and Piemont and the amplitude of movement. The evaluation was a pre application type, after 15 days and 30 days of application of BTA being associated with physiotherapy with kinesiotherapeutic exercises. Results and Discussion: Reports in the study of the maximum effect of BTA around 15 days after the application, although other authors consider that the BTA reaches its maximum effect in 1 to 4 weeks, which indicates that the toxin may have reached its maximum effect in 15 days in this study, justifying the data that were obtained. Based on the data obtained in this study, the muscle group that showed the highest gain was the one from adductors of hips together with the decrease of tone of the muscle group, It was possible to notice a significant increase concerning the angle of this adductor. Conclusion: The application of BTA itself, however, is not able to bring satisfactory results. Physiotherapy associated with the application of BTA had influence on the increase of amplitude of movement and decrease of spasticity. It is believed that the therapy favored the stretching of muscles and the joint positioning, providing more adequate and functional length of the muscle groups.